Plastome sequencing of a 167-year-old herbarium specimen and classical morphology resolve the systematics of two potentially extinct grass species. (28th August 2020) - Hardion, Laurent; Verlaque, Régine; Kaymak, Esra; Vila, Bruno; Haan-Archipoff, Gisèle; Martinez Martin, Marion; Tournay, Frédéric; Migliore, Jérémy
Abstract: The systematics of Arundinoideae (Poaceae), a subfamily long considered as a dustbin group, has been progressively resolved in recent decades. The last members incertae sedis of Arundinoideae are two African species not observed for > 150 years and currently studied only on the basis of old herbarium specimens. Based on the sequencing of its whole plastid genome, Leptagrostis schimperiana was placed in the monophyletic Crinipedeae (Arundinoideae) in the grass plastome phylogenetic tree. To date, whole plastome sequencing based on a 167-year-old herbarium specimen is a new record. Using a morphological cladistic approach based on 51 morphological and anatomical characters, we confirmed the position of Leptagrostis schimperiana and showed that Piptophyllum welwitschii is also a member of Crinipedeae.